Evaluation of Bacillus thuringiensis-based bioinsecticide impacts on arthropod biodiversity in the intercropping system - Yulia Pujiastuti (The East Java Biological Society, 2019)
The intercropping system is intended to increase vegetable production. However, The presence of pests reducing production levels is a challenging constraint and should be controlled. In this study, Controlling insect pests will be evaluated by Bacillus thuringiensis-based bioinsecticide. The purpose of the research was to investigate the biodiversity of insect pests and their natural enemies in intercropping systems (cucumber and long beans), applied by B. thuringiensis-based bioinsecticide, chemical insecticide, and no-both application. Observation of existing insect-plant canopy was directly observed, and those on soil surface were observed by pitfall traps and yellow trays, as well. The research was performed in the experimental farm of the Sriwijaya University Faculty of Agriculture, Indralaya Campus, Ogan Ilir, South Sumatra, from July until October 2018. Results indicated three ecological roles of insects, namely predators/carnivores, pests/herbivores, and pollinators. Other insects and arthropods obtained from direct observation sampling method identified ten orders, but treatments of B. thuringiensis-based bioinsecticide resulted in 29 families of insects, chemical treatment was 17, and control (no treatment) was 32 families. B. thuringiensis-based bioinsecticides may be used in the intercropping system since it causes the highest biodiversity (H '= 2.96), high predator population (45%) and low pest population (41%) compared to other treatments.